Correlation between P16/Ki67 in cervical cytology and diagnosis of cervical intraepithelial neoplasia 2-3 in Thai women infected with high-risk types of human papillomavirus - Manasawee Srisuttayasathien; Nuttavut Kantathavorn; Taksa Luasiripanthu; Supinda Petchjorm; Jidapa Samrarn; Pornprom Ittiamornlert; Wasanai Krisorakun; Asama Vanichtantikul; Thanita Wetcho; Siriporn Saeloo (Elsevier, 2024)
Objectives: The addition of p16/Ki-67 dual immunostaining to human papilloma virus (HPV) screening tests has been shown to increase the detection rate of high-grade cervical intraepithelial neoplasia. Thus, the aim of this study was to evaluate the accuracy of p16/Ki67 dual staining in the detection of cervical intraepithelial neoplasia 2 (CIN2+) in women with high-risk HPV infection. Materials and methods: A cross-sectional study was conducted between August 2017 and August 2019 at the Chulabhorn Hospital in Bangkok, Thailand. Women aged 20-70 years who underwent co-testing and tested positive for high-risk (HR) HPV (N = 215) were invited to participate in the study. P16/Ki67 testing was performed on residual cytological materials. Colposcopic biopsies were performed on all patients, and the results were correlated with positive or negative p16/Ki-67 test results. Results: The sensitivity and specificity of p16/Ki-67 dual staining in the detection of CIN2+ in the women with HR HPV infection were 74.4 % and 63.4 %, respectively. Compared with liquid-based cytology (LBC), p16/Ki67 cytology had similar sensitivity (p = 1.000) and specificity (p = 0.561) to LBC for detecting CIN2+. Conclusion: In this study, p16/Ki67 dual staining in HPV triage demonstrated a test performance similar to that of LBC.